القضاء والقدر في قصة موسى عليه السلام وما يستفاد منه في واقعنا المعاصر: قراءة تحليلية: The Concept of Fate and Destiny in the Story of Prophet Moses (Peace Be Upon Him) and its Relevance in our Contemporary Reality: An Analytical Reading - Harun, Uthman Thani; Syed Abdul Rahman, Syed Muhammad Helmi; Salim Al-Qatawnah, Muhammad Abdul Halim (Al-Basirah Journal, 2022)
This paper discussed about of what our contemporary society can benefit from the Divine decree and Predestinations mentioned in the story of Prophet Musa, peace be upon him. There is no doubt that fate is one of the most prominent of the doctrinal issues of the occult in the Islamic faith. It raises many questions and problems, a slip of the feet for many Islamic groups, and a course that led many Islamic sects and individuals have gone astray. Because they tried to see the secrets of the Allah’s decree, which is from the occult, and it is one of the most special characteristics of the unseen realm, whose knowledge is left in the Hands of Allah himself. No one has ever seen his unforeseen except those whom he wished from his messengers and prophets. There is no doubt that the issue of predestination and will are very complicated. Therefore, the Almighty Allah did not leave His servants bewildered and perplexed like this without guidance, He guided the People so that Satan would not dominate them. Almighty Allah forbid that he does this to his servants. Rather, he resurrected them, as soon as they held on to Him, they would never perish. Anyone who contemplates the verses of the story of the Prophet Musa, peace be upon him, in the Qur’an, acquires accurate information for himself with some hidden goals in divine decree and predestination. The Man's belief in the unseen increase’s strength of his faith, until the strength of his faith is equal, and his certainty of the sensations that surround him and see them in his days and nights. The paper talks about what we benefit from in our contemporary reality, with some of the goals of divine decree and destiny that lie in the story, to renew our belief in the unseen and to enlighten us the way in our submission to the Allah’s divine decree and His power over us. There is no doubt that this renews our faith every day.